Pengaruh Pengawasan Dan Disiplin Kerja Terhadap Kinerja Pegawai Negeri Sipil Pada Dinas Perindustrian Perdagangan Energi Dan Sumber Daya Mineral Provinsi Sumatera Utara - Mutiah Khaira Sihotang (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to determine the influence of supervision and work discipline on the performance of civil servants at the Department of Industry, Trade, Energy and Mineral Resources, North Sumatera Province. The method in this research uses a descriptive quantitative approach. The total sample for this research was 68 respondents, namely civil servants of the Department of Industry, Trade, Energy and Mineral Resources of North Sumatera Province. The data source used in this research is primary data obtained by distributing questionnaires to respondents. The data analysis techniques in this research are data quality testing, classical assumption testing, multiple linear regression testing and hypothesis testing carried out using SPSS version 26 software. The results of the research show that simultaneously, supervision and work discipline have a positive and significant effect on employee performance as evidenced by the fcount value of 103,096 > ftable of 3,14 and a significance value of 0,000 < 0,05. Based on the results of the R-Square coefficient of determination (R2) test, it is known that 76% of the dependent variable, namely employee performance, can be influenced by the independent variables, namely supervision and work discipline. Meanwhile, the remaining 24% is influenced by other variables not examined in this research.